Acompanhamento do processo produtivo de cachaça artesanal - Macena, Samuel Vinícius Holanda (Universidade Federal Rural do Semi-Árido, 2021)
Cachaça is a genuinely Brazilian drink, with its first production records dating back to the 16th century. Since then, the number of drink producers, whether cachaça or aguardente, has exceeded 1,000 and the number of registered brands exceeds 5,000. Although the legislation does not differentiate cachaça between industrial and artisanal means, in practice there are differences, especially in the stages of the process. In the artisanal production process, the fermentation is done in a natural way and, later, the distillation is done in copper stills. This work was done during the internship activities developed at the company Nova Malhada, which produces cachaça by hand in the municipality of Apodi-RN. The alembic was founded a few years ago in order to revive the history of cachaça Malhada Vermelha, which for a long time was produced in the municipality of Severiano Melo – RN. This work aims to evaluate the quality control activities in the Nova Malhada company. Among the activities developed is the implementation of good manufacturing practices (GMP), which aim to bring improvements in quality and competitiveness to the final product. It is also proposed to monitor the production of cachaça in all its stages, mainly sugarcane crushing, fermentation and distillation, and carrying out physicochemical analyzes to check the quality of the final product. The internship period at Nova Malhada was of great value for the development of knowledge developed during the course, mainly in the areas of distillation and fermentation. After this period, some improvements were suggested in the points where it was observed that it was necessary for the best development of the still.
Keywords: Cachaça; Qualidade; Artesanal; ENGENHARIAS::ENGENHARIA QUIMICA